Assessment of the prevalence of rheumatic ailments among people aged 18-25 years - Kitowska, Wioleta (Pedagogy and Psychology of Sport, 2016)
Introduction Rheumatic diseases, along with other diseases of the musculoskeletal system are among the most common chronic diseases in the world. Factors predisposing to rheumatic diseases are genetic factors, external physical factors as well as the so-called "civilization factor" - an effect of modern "civilized" life. It is suspected that rheumatic diseases are responsible for absorbing the largest portion of the GDP of all diseases. Materials and Method The study was conducted using a diagnostic survey. The study population consisted of university students in the age group of 18-25 years. The tool used to perform the test was an original questionnaire, which was distributed using the CAWI technique. The number of respondents amounted to 308 persons. Results As many as 38% of respondents declared visiting a doctor due to ailments of the skeletal system, which were not a result of injury. A larger proportion of women (40%) than men (30%) declared such visits. Most people do not have bone or joint deformities that are not caused by injury (59%). More women (31%) than men (29%) acknowledged an existence of such defects. More than half of both women (50%) and men (52%) have experienced joint stiffness or difficulty moving said joints. Conclusions Young adults often show symptoms that may be associated with rheumatic diseases. However, only a small percentage have seen a medical professional because of them, and even less have done tests aimed at diagnosing a rheumatic disease. The low rate may be due to lack of knowledge about rheumatic diseases. It is possible, that more people live to fall ill at an earlier age.